Analysis of Sling Tension on the Lifting Process of Riser Support Jacket on Installation Phase - Mahardi, Rifki; Hadiwidodo, Yoyok Setyo; Prastianto, Rudi Walujo (International Journal of Offshore and Coastal Engineering (IJOCE), 2024)
The increasing exploration and exploitation of oil and gas in the deep sea has led to an increasing need for new technologies to support these activities. In this study, a riser support structure in the form of a jacket is used to support the riser so that the stress can be minimized. Like the jacket structure in general, this riser support structure can be installed using various methods, including the lifting method. This study discusses the stress in the sling when the lifting process is carried out. The crane barge used in this study was first modeled using MOSES Software to determine how the barge moves when the lifting process is carried out. The result of the barge movement analysis is a Response Amplitude Operator (RAO). In the sway, heave and roll movements, it is known that the maximum value is at 90° heading, while in other movements, it varies. The riser support structure is modeled using SACS Software to determine the center of gravity, then the sling length is calculated. From the calculation, the sling length at lifting point 1 is 34,10 m, lifting point 2 is 34,14 m, lifting point 3 is 36,08 m, and lifting point 4 is 36,10 m. The lifting model is input into the OrcaFlex Software to analyze the sling stress. The analysis was performed in five loading directions, namely 0°, 45°, 90°, 135°, and 180°. The maximum stress occurs in the loading direction of 90°, with the result that sling 1 is 1932,70 kN, sling 2 is 1905,65 kN, sling 3 is 1161,64, and sling 4 is 1193,65 kN.